2019
DOI: 10.2196/13715
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Study of HIV Prevention in the Era of Pre-Exposure Prophylaxis Among Vulnerable HIV-Negative Gay and Bisexual Men, Transmen, and Transwomen Who Have Sex With Men: Protocol for an Observational Cohort Study

Abstract: BackgroundGay, bisexual, and other men who have sex with men continue to bear a large burden of the HIV epidemic in the United States and are among the only populations with increasing incidence in recent years.ObjectiveThe Together 5000 (T5K) Study aimed to enroll a US-based, racially diverse sample of HIV-negative men, transmen, and transwomen who are not on pre-exposure prophylaxis (PrEP) into an observational cohort to inform the design, implementation, scale-up, and evaluation of HIV prevention programs.M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
(19 reference statements)
0
31
0
Order By: Relevance
“…We applied internet-based strategies that have been demonstrated to be effective for recruiting and following large and geographically diverse online cohorts. [2][3][4]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied internet-based strategies that have been demonstrated to be effective for recruiting and following large and geographically diverse online cohorts. [2][3][4]…”
Section: Methodsmentioning
confidence: 99%
“…[76] Data will be presented as flat text files (CSV) formatted for compatibility with the New York Times county-level longitudinal case load dataset [3], including date, county, state, and fips code. A GitHub Actions script will perform weekly updates of the repository and its associated GitHub Pages site, automatically incorporating all new submissions from the previous week.…”
Section: Data Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected as part of the Together 5000 study—a national, internet-based cohort study of men, trans men and trans women in the United States. 9 10 Enrollment began in October 2017 using ads on men-for-men geosocial sexual networking phone applications and concluded in June 2018. Eligibility criteria for the study are shown in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, the National Institutes of Health funded multiple research sites to conduct Limited Interaction Targeted Epidemiology (LITE) to Advance HIV Prevention [32]. Funded sites are each following thousands of participants through 2022, and at-home HIV testing is an integral component of study participation [32][33][34]. HIV prevention studies operating remotely have the option of using rapid or mail-in HIV testing.…”
Section: Introductionmentioning
confidence: 99%